2003
DOI: 10.1097/01.ju.0000082252.49374.e9
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes And Bacteria In Men With Chronic Prostatitis/Chronic Pelvic Pain Syndrome Compared To Asymptomatic Controls

Abstract: Men with CP/CPPS have significantly higher leukocyte counts in all segmented urine samples and EPS but not in semen as compared to controls. There is no difference in rates of localization of bacterial cultures for men with CP/CPPS compared to control men. The high prevalence of WBCs and positive bacterial cultures in the asymptomatic control population raises questions about the clinical usefulness of the standard 4-glass test as a diagnostic tool in men with CP/CPPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(107 citation statements)
references
References 6 publications
3
98
1
5
Order By: Relevance
“…However, recent studies have demonstrated that the presence of bacteria in prostate has no relationship with symptoms 40 and that the presence of bacteria in prostatic secretions is identical in men with CP/CPPS and age-matched asymptomatic men. 41 The current body of medical literature is almost devoid of information pertaining to orgasmic dysfunction and orgasm-associated pain in men. The neurophysiology of the male orgasm is even less well understood than that of erection.…”
mentioning
confidence: 99%
“…However, recent studies have demonstrated that the presence of bacteria in prostate has no relationship with symptoms 40 and that the presence of bacteria in prostatic secretions is identical in men with CP/CPPS and age-matched asymptomatic men. 41 The current body of medical literature is almost devoid of information pertaining to orgasmic dysfunction and orgasm-associated pain in men. The neurophysiology of the male orgasm is even less well understood than that of erection.…”
mentioning
confidence: 99%
“…Confounding the diagnosis is the fact that up to 8% of men with presumed CP/CPPS and no history of positive urinary tract infections have positive prostate localization cultures. However, a similar number of asymptomatic men will have positive localization cultures as well [21].…”
Section: Diagnosismentioning
confidence: 99%
“…Therefore, infection has been commonly assumed by patients and clinicians alike to be the cause of the symptoms, both historically and to this day. In the Chronic Prostatitis Collaborative Research Network (CPCRN) study, using the 4-glass urine test for localization, men with CP/CPPS and asymptomatic controls showed almost identical numbers of bacteria isolated from urine, prostatic fluid, and post-prostate massage urine [5]. Eight percent of men had uropathogenic bacteria and roughly 70% had some form of bacteria in each group.…”
Section: Infectionmentioning
confidence: 99%